Antimicrobial polyketides from Trichoderma koningiopsis QA-3, an endophytic fungus obtained from the medicinal plant Artemisia argyi. Issue 81 (3rd November 2017) - Shi, Xiao-Shan; Wang, Dun-Jia; Li, Xiao-Ming; Li, Hong-Lei; Meng, Ling-Hong; Li, Xin; Pi, Yan; Zhou, Xing-Wang; Wang, Bin-Gui
Abstract : Five new and two known antimicrobial polyketides were identified from endophytic Trichoderma koningiopsis QA-3. Abstract : Artemisia argyi is broadly cultivated as a medicinal plant in Qichun of Hubei province in central China. Five new fungal polyketides (1–5 ) and two known analogues (6 and7 ) were isolated and identified from the culture extract of Trichoderma koningiopsis QA-3, an endophytic fungus obtained from the inner tissue of Artemisia argyi that was collected from Qichun. Their structures were elucidated by detailed interpretation of the spectroscopic data and the structures and absolute configurations of compounds1–4 were confirmed by X-ray crystallographic analysis. Compounds1–3 are tricyclic polyketides possessing octahydrochromene framework and having ketal unit in their structures, while compounds4 /7 and5 /6 are related bicyclic and tricyclic analogues, respectively. The antibacterial activities against human pathogen E. coli and seven marine-derived aquatic pathogens as well as against eight agro-pathogenic fungi for each of the isolated compounds were evaluated. Compounds1–7 showed activity against human pathogen Escherichia coli (each with MIC 64 μg mL −1 ), while1 and7 inhibited most of the tested aquatic bacteria and agro-pathogenic fungi (MICs ranging from 4 to 64 μg mL −1 ), respectively.